Cavity beam position monitor at the interaction point region of accelerator test facility 2 - Kim, Y; Bett, D; Kraljevic, N; Burrows, P; Christian, G; Davis, MR; Perry, C; Boogert, S; Lyapin, A; Honda, Y; Tauchi, T; Terunuma, N; et al. (2013)
Nanometre resolution cavity beam position monitors (BPMs) have been developed to measure the beam position and to be linked to control the beam position stability within a few nanometres in the vertical direction at the focus, or Interaction Point (IP), of the Accelerator Test Facility 2 (ATF2). In addition, for feedback applications a lower-Q and hence faster decay time system is desirable. Two cavity so-called IP BPMs have been installed inside the IP chamber at the ATF2 focus area. To measure the resolution of IPBPMs two additional C-band cavity BPMs have been installed one upstream and one downstream of the IP. One cavity BPM has been installed at an upstream vertical image point of the IP. The performance of the BPMs is discussed and the correlation between the IP and image point positions is presented along with a discussion of using these BPMs for position stabilisation at the IP. Copyright © 2013 by JACoW.